ANALISIS KEBUTUHAN STRATEGI KOMUNIKASI VISUAL KAMPANYE PELESTARIAN KESENIAN ONDEL-ONDEL BETAWI - Irfandi Musnur; Venna Amelia (Narada : Jurnal Desain dan Seni, 2020)
Indonesia is famous for its cultural diversity starting from the diversity of tribes, languages, religions, and others. One of the ethnic groups in Indonesia is the Betawi ethnic group, which is an Indonesian ethnic group whose residents generally live in Jakarta. The Betawi tribe is a descendant tribe of residents who lived in Batavia since the 17th century. One of the cultures owned by the Betawi tribe is ondel-ondel, where ondel-ondel consists of 2 giant dolls in red and white that make one of the cultural icons owned by the Betawi tribe. Ondel-ondel at this time is easy to find around us or in the capital city of Jakarta, we often see ondel-ondel walking around the street accompanied by music that is surrounded by several people as driving music carts and there are also those who hold a container to get a purse coffe rupiah. Given this, some people assume that the cultural value of the Betawi people has decreased, the use of the method used is a qualitative method. The desired results can determine the right media for the ondel-ondel art preservation campaign as well as knowledge to the public about the importance of ondel-ondel art.